Wild maps for curious minds : 100 new ways to see the natural world - Higgins, Mike (Journalist) (The Experiment, 2022)
Which nations have launched animals into space? Where are the world's cat people? How many humans live in high-risk zones for natural disasters? How far do you have to travel to hug all fifteen of the world's oldest trees? Where in the world do snakes live--or better yet, where can you avoid them?! Find the thought-provoking answers to these questions and many more in Wild Maps for Curious Minds. This infographic atlas of nature's most impressive wonders and eye-popping oddities is bursting with discovery (Where's the most remote place on Earth?), whimsical insight (Which animals have launched into space?), and startling revelations (How much forest have we destroyed?) that will change the way you see the natural world--and that celebrate our planet and the plants and animals with whom we share it.